The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.mp.4001268
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a single nucleotide polymorphism in the promoter of the G protein receptor kinase 3 gene is associated with bipolar disorder

Abstract: In a genome-wide linkage survey, we have previously shown evidence suggesting that the chromosome 22q12 region contains a susceptibility locus for bipolar disorder (BPD). Two independent family sets yielded lod scores suggestive of linkage at markers in this region near the gene G protein receptor kinase 3 (GRK3). GRK3 is an excellent candidate risk gene for BPD since GRK3 is expressed widely in the brain, and since GRKs play key roles in the homologous desensitization of G protein-coupled receptor signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Collectively, these observations suggest that the defective GRK3 mRNA expression in P3 cells arises from an impaired synthesis, either directly due to a polymorphism in transcriptional regulatory regions or indirectly due to the altered expression of a transcription factor that modulates GRK3 expression. Several SNPs were identified in the putative promoter region of GRK3, which may affect the regulation of gene expression, and were associated with bipolar disorder in families of northern European Caucasian ancestry (44,45). We did not identify any specific SNP in the minimal putative promoter region of GRK3 in P3 cells.…”
Section: Figurementioning
confidence: 79%
“…Collectively, these observations suggest that the defective GRK3 mRNA expression in P3 cells arises from an impaired synthesis, either directly due to a polymorphism in transcriptional regulatory regions or indirectly due to the altered expression of a transcription factor that modulates GRK3 expression. Several SNPs were identified in the putative promoter region of GRK3, which may affect the regulation of gene expression, and were associated with bipolar disorder in families of northern European Caucasian ancestry (44,45). We did not identify any specific SNP in the minimal putative promoter region of GRK3 in P3 cells.…”
Section: Figurementioning
confidence: 79%
“…The gene for regulator of G-protein signaling 4 (RGS4) was initially brought into attention by a microarray study and recently reported to be associated with schizophrenia. 30 Selecting candidates based on expression data also led to the detection of associations of Gprotein-coupled receptor kinase3 (GRK3) 31 and other promising gene 32 with bipolar disorder. Altered expression level of G protein AS and AI2 subunits (GNAS, GNAI2) in the post-mortem brains from bipolar or lithium receiving subjects has also been reported, 33 although variants in the former gene are not apparently associated with bipolar disorder.…”
Section: Neurotransmission Systemsmentioning
confidence: 99%
“…Recent reports describing the putative promoter region of the GRK3 gene have suggested the presence of binding sites for the transcription factors, Sp-1 and Ap-2, in the GRK3 promoter region (Barrett et al, 2003). Therefore, we examined the nuclear translocation of these transcription factors in response to EPI (0.3 M) treatment.…”
Section: Regulation Of Grk3 Expression 53mentioning
confidence: 99%
“…GRK2 promoter-luciferase reporter constructs have demonstrated that phorbol esters, ␣ 1 -AR agonists, and serum stimulation (Ramos-Ruiz et al, 2000;Theilade et al, 2005) increase GRK2 expression at the transcriptional level. However, there are relatively few reports of the selective increase in GRK3 expression (Dautzenberg and Hauger, 2001;Dautzenberg et al, 2002), and the GRK3 gene promoter has not been characterized but is predicted to lie in the genomic region immediately 5Ј to exon 1 (Barrett et al, 2003).…”
mentioning
confidence: 99%